PELANGGARAN KODE ETIK KEDOKTERAN PADA KASUS PENGANGKATAN INDUNG TELUR PASIEN SECARA SEPIHAK DI RS. GRHA KEDOYA JAKARTA BARAT - Heri Setiawan; Devka Octara Putera; Nicolaas Sugiharta (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2018)
Ethics is the knowledge of what is good and bad and moral rights and obligations. When derived from the ancient Greek words ethos which in the singular means good customs, customs, or morals. Ethics is a good and bad teaching that has been generally accepted regarding attitudes, rights behavior, obligations and so on. Ethics is always related to moral words, which are measures that have been accepted by a community. In the medical world there are also found teachings on ethics and morals that are used as guidelines for carrying out their duties and obligations in serving the community. When the doctor violates the prevailing ethics and morals, sanctions will be imposed, either by professional groups that establish the code of ethics, or be subject to legal sanctions that will be processed and dropped by authorized legal institutions. From the point of view of criminal law, malpractice issues are more emphasized and based on consent or approval. Any invasive medical action taken by a doctor without the consent of the patient, can be sued as a criminal act of maltreatment, especially if using anesthesia. As long as the medical action provided by the doctor to the patient is carried out correctly according to professional standards and standard operating procedures, even though the results of the medical action are not as expected, it is not considered a malpractice. The purpose of this study is so that people can understand that every doctor's actions must be in accordance with procedures and should not be done if they do not get approval from the patient if it is related to practice. Writing method uses data obtained from library material called secondary data. Secondary data includes primary law (UU), secondary (article), and tertiary materials. Legal research that we do by researching library material or secondary data can be called normative legal research. Our group used normative legal research in which our group would conduct a search to investigate cases of unilateral removal of the patient's ovaries at the hospital. Grha Kedoya West Jakarta.